Compassion Education in Guarding Children's Psychological Development in Orphanages - Madani, Aris; Rahmatullah, Azam Syukur (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This study aims to analyze the impact of compassion-based education on the psychological development of children in orphanages. This research uses a type of field study research with a qualitative approach. This research was located at the Putri 'Aisyiah Orphanage Yogyakarta. Research data were obtained from observations, interviews, and required documents with 3 informants, namely the management of the panti, the foster parents, and musrifah. The collection of research data was carried out In the first stage, the selection of the location of the orphanage and the identification of the main participants, caretakers, foster parents, and musrifah. Data collection was conducted through three main methods: in-depth interviews, observation, and analysis of documents such as caregiver diaries and child development reports. The next stage is the data coding process, where the collected data is transcribed and encoded thematically. Each data segment is categorized based on indicators of compassion, such as emotional attention, psychological support, positive interactions, and fulfillment of basic needs. Next, thematic analysis is conducted to find patterns and relationships between themes. These findings were verified through data triangulation by comparing results from interviews, observations, and document analysis. This process ensures consistency and increases the validity of findings at the final stage, interpretation, and conclusion. The thematic analysis results were interpreted to assess the effectiveness of compassion education in orphanages. The conclusion shows that children who still struggle to obey the rules and daily activities in the orphanage have successfully implemented compassion education. There needs to be a more comprehensive understanding of foster parents so that children in orphanages can grow up psychologically healthy.